The Jumping Ring as an inquiry project: A learning-opportunities perspective - Langley, Dorothy Vivienne; Arieli, Rami (Journal of physics. Conference series, 2021)
Incorporating authentic inquiry into high school physics instruction has been advocated for over a century, and has become an integral part of science instruction standards world-wide. The Inquiry Physics program in Israel is a 3 year, elective course for high school physics majors. Students acquire scientific research knowledge and skills primarily by performing inquiry projects of increasing complexity and finally devoting a full year to researching a significant issue under the guidance of expert mentors. Selecting a suitable research topic requires management of tensions related to complexity of content, experimental practice, data analysis and project logistics. The Jumping Ring phenomenon, in which a metal ring is launched vertically due to a magnetic force generated by a coil carrying AC current, was the subject of a final inquiry project in 2018. The phenomenon offers dramatic appeal and motivation, rich inquiry options and diverse experimental skills, considerable knowledge consolidation and extension (magnetic fields and forces, electromagnetic induction and AC circuits) along with technological and logistic manageability. Mentoring the project involved exploring an uncharted learning-opportunities’ path, balancing direct instruction and independent exploration, as well as dealing with time constraints and variations in the project team’s attendance and commitment.